Cognitive Presence in Blended Learning: An Investigation of Students’ Perceptions and Expectations - Dilla Sufianita; Primardiana Hermilia Wijayati; Mirjam Anugerahwati (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2023)
This study examines English students’ perceptions and expectations of the cognitive presence in a blended learning environment. It utilized the sequential explanatory strategy which combined the survey design and interview to obtain the data. The results indicate that students’ perceptions derived from experience are different from their expectations at some points. Few students take the initiative to prepare actively by reading more information related to the course or establishing learning goals. Additionally, students who do not prioritize preparation tend to depend solely on their teachers for course explanations. The findings suggest that self-regulation is critical to effective learning and that students need to explore and gather information themselves to succeed. Furthermore, students expect to search for relevant information online and participate in discussions to stimulate critical thinking and enrich their learning experience. These results can assist teachers and instructional designers in designing blended learning environments that promote students' cognitive presence and foster effective learning.